Cell mediated rejection. - Wood, K; Zaitsu, M; Goto, R (2013)
Rejection is the major barrier to successful transplantation and usually results from the integration of multiple mechanisms. Activation of elements of the innate immune system, triggered as a consequence of tissue injury sustained during cell isolation or organ retrieval as well as ischemia-reperfusion, will initiate and amplify the adaptive response. For cell mediated rejection, T cells require multiple signals for activation, the minimum being two signals; antigen recognition and costimulation. The majority of B cells require help from T cells to initiate alloantibody production. Antibodies reactive to donor HLA molecules, minor histocompatibility antigens, endothelial cells, red blood cells, or autoantigens can trigger or contribute to rejection early as well as late after transplantation.